3D Honey-Comb like Nitrogen Self-Doped Porous Carbon Networks for High-Performance Electrochemical Detection of Antibiotic Drug Furazolidone. Issue 4 (7th April 2021) - Ramadhass, Keerthika Devi; Ganesan, Muthusankar; Chen, Tse-Wei; Chen, Shen-Ming; Ali, Mohammad Ajmal; Habila, Mohamed A.; El-Marghany, Adel; Sheikh, Mohamed
Abstract : Herein we report the preparation of porous activated carbon from the biomass waste material, such as Borassus flabellifer (Asian palmyra palm) shell as a carbon precursor. The structural, morphological studies reveal the formation of the 3D-graphene like porous activated carbon nanosheet (3D-PAC) from the Borassus flabellifer . Interestingly, the 3D-PAC was self-doped with nitrogen, which was confirmed from the XPS analysis. The structural, morphological, and electrochemical properties of 3D-PAC were analyzed using various physiochemical and electrochemical methods. Then for the first time, we probed the analytical behavior of 3D-PAC modified glassy carbon electrode (3D-PAC/GCE) to detect furazolidone (FZ, antibiotic drug). The effect of experimental parameters like modifier loading concentration/volume, pH, analyte accumulation time, scan rate, and sample concentration was studied based on FZ's reduction peak current. The developed drug sensor exhibited excellent FZ detection performance, with a wide linear range from 0.5 to 290 μ M, a limit of detection (LOD) of 0.5 nM, and appreciable sensitivity of 5.05 μ A μ M −1 cm −2 . Further, the proposed sensor was also well performed in real sample (human urine) analysis with good recovery results.